Effects of different substrates on formation and development of bulblets in Lilium sp - Leyla Eken (Anadolu Tarım Bilimleri Dergisi, 2018)
ABSTRACT Although lilium sp. bulb growth has been mostly performed in soil, there are problems in production of bulbs because of physical and chemical properties of soil, diseases and pests. Properties of soil also effects time of formation of suitable bulb size to form flowers in lilium bulb. In this study it was aimed to determine the effects of different alternative substrates on bulblet formation and development to sole the probles on propagation of new bulblets in Lilium.Study was performed in spring, 2011 and Lilium LA hybrids cv. “Ceb Dazzle” was used. In this study, (1) chestnut shell + perlite, (2)peanut shell + perlite, (3)sand + peanut shell, (4) perlit, (5) chestnut shell + sand, (6) soil + organic manure + peat (control), (7) peat + sand, (8) cocopeat, (9) volcanic tuff were used as substrates. Lilium plants were grown in 60 L volumed plastic boxes filled with substrates. In order to determine the properties of bulb development, roots which are formed on bulbs and stems were analyzed. And in order to determine the formation and development of bulblets, bulblets formed in mother bulb and plant stem were analyzed in terms of number of bulbs, weight, length and height.As a result of this research, instead of there weren’t any bulblet formation on the mother bulbs, it was observed that there is bulblet formation on plant stems and they were analized. The highest number of bulblet formation was obtained in Sand+Peanut Shell substrat mix with the 17.5 number/bulb. It is determined that, the best results in terms of average weight, lenght and height diameter of bulblets, were obtained on Sand+Peanut Shell (12.387 g,14.34 mm lenght, 14.54 mm height) and Peat+Sand (8.983 g, 13.31 mm lenght ve 14.42 mm height) substrats.